Composition for forming a back electrode comprising a conductive polymer and method for manufacturing the same
By using a composition of a water-based conductive polymer solution and a specific adhesive, a three-dimensional network structure is formed through hydrolysis and dehydration condensation reaction, the problems of unstable storage stability and surface resistance changes of the conductive polymer composition are solved, and the problem of instability in the change of the conductive polymer composition is achieved. High hardness and stable surface resistance effect.
Patent Information
- Application Number
- CN202311500460.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-07
- Filing Date
- 2023-11-13
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-11-13
AI Technical Summary
When using conductive polymer compositions in the prior art, the storage stability is poor, the surface resistance is unstable with time, and cracks are prone to occur after heating and curing, which affects the long-term maintenance of physical properties.
Compositions of water-based conductive polymer solutions, specific binders (such as mixtures of MTES and DMDES) and solvents are used to form a three-dimensional network structure through hydrolysis and dehydration condensation reactions to improve the hardness and surface resistance of the composition. stability.
The high hardness and stable surface resistance of the conductive polymer composition are achieved, the shelf life is extended, and the occurrence of cracks is reduced after heating and curing, and the long-term stability of physical properties is maintained.
Smart Images

Figure CN118146703B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a composition for forming a back electrode and a method for manufacturing the same, and more specifically, to a composition for forming a back electrode and a method for manufacturing the same, which comprises a water-based conductive polymer solution, an adhesive and a solvent, thereby being able to maintain excellent hardness and surface resistance and having stable physical properties.
[0002] The composition of the present invention has superior characteristics compared to existing compositions in terms of change in surface resistance over time and storage stability. Background Art
[0003] On panels such as liquid crystal displays, that is, on color film substrates, an antistatic layer needs to be formed to prevent static electricity from being generated with the outside of the electrode, etc. Various materials are currently used to form the antistatic layer. Specifically, ITO (Indium-Tin-Oxide: Indium Tin Oxide) or IZO (Indium-Zinc-Oxide: Indium Zinc Oxide) is currently used, but these materials require a vacuum deposition process, and, in terms of the characteristics of these materials, although they have excellent resistance and surface hardness, they have the disadvantage of poor transmittance.
[0004] In addition, the prices of ITO or IZO continue to rise, and the cost of the deposition process is also very expensive, so it is necessary to develop new materials that can replace these materials.
[0005] Therefore, various attempts have been made to use conductive polymers that can overcome these disadvantages and are more flexible and have higher permeability than metal oxides. However, in the case of compositions using conductive polymers, storage stability deteriorates and changes in coating films over time are not as satisfactory as those of metal oxides.
[0006] The first unstable factor is the instability of the shelf life of the coating liquid composition. When a dry coating film is formed immediately after the composition is manufactured, the prior art has excellent adhesion to the glass substrate and a stable surface resistance value on the surface of the dry coating film. However, as the storage time of the coating liquid composition as a liquid becomes longer (increase in circulation time), when the coating liquid is applied after a certain period of time to form a dry coating film, the problem of decreased adhesion of the dry coating film and increased surface resistance value will occur. Since the shelf life of the prior art that can ensure stable physical properties is very short, it needs to be used within a limited time after manufacturing.
[0007] The second unstable factor is the change of the dried coating film over time. After the dried coating film is heated and cured, its surface resistance also changes over time. Generally, in the early stage of the dried coating film, its surface resistance value is good, but over time, the hardness of the dried coating film increases or fine cracks appear, showing a tendency for the surface resistance to increase. For the physical properties of the dried coating film, it is particularly important to be able to maintain its characteristics for a long time and not change over time.
[0008] Therefore, it is necessary to develop a new composition as a silane composition for liquid crystal panels containing a conductive polymer, which can not only extend the shelf life but also maintain stability and surface resistance or hardness and can be used in the manufacturing process of the panel.
[0009] Prior art literature
[0010] Patent Literature
[0011] (Patent Document 0001) Korean Patent Application No. 2013-0154635 Conductive composition for forming a back electrode of a liquid crystal display device
[0012] (Patent Document 0002) Korean Patent Application No. 2015-0191575 Method for Manufacturing Antistatic Film and Method for Manufacturing Display Device Summary of the invention
[0013] Problems to be solved by the invention
[0014] In order to solve the above problems of the prior art, the present invention aims to provide a composition for forming a back electrode having excellent physical properties of hardness and surface resistance and a method for manufacturing the same. In particular, the present invention aims to maintain stable surface resistance and hardness even when a conductive polymer is used instead of metal ions or surfactants, and to completely cure the coating film when heated and cured even without using a separate curing agent.
[0015] Methods used to solve problems
[0016] In order to achieve the above object, the present invention provides a composition for forming a back electrode, which comprises a water-based conductive polymer solution, a binder and a solvent.
[0017] In addition, the present invention provides a method for manufacturing a composition for forming a back electrode, which includes: a) a step of mixing a binder and a solvent to prepare a mixed solution; b) a step of adding a conductive polymer solution to the mixed solution; and c) a step of hydrolyzing the conductive polymer and the binder in the solution manufactured in step b).
[0018] In addition, the present invention provides a method for manufacturing a back electrode, which includes: a) a step of coating a composition for forming a back electrode on a substrate; b) a step of heating and curing the coated substrate; and c) a step of reacting the composition in such a way that it has a three-dimensional network structure through a condensation reaction.
[0019] Effects of the Invention
[0020] The composition for forming a back electrode of the present invention has the following advantages: even if a conductive polymer is used, its surface hardness is high, and the stability of surface resistance over time and storage stability are excellent. Therefore, it can replace the existing back electrode using metal oxide and can be used in various liquid crystal panels, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a diagram showing the change of the molecular structure of TEOS before and after hydrolysis.
[0022] Figure 2 This is a diagram showing an example of the dehydration condensation reaction of TEOS (Si-(OH)4) after hydrolysis.
[0023] Figure 3 Schematic diagram showing a dried (cured) TEOS coating film after a dehydration condensation reaction.
[0024] Figure 4 It is a graph showing the change of solid percentage (%) according to the number of dehydration condensation reactions.
[0025] Figure 5 : is a diagram illustrating the structures of four types of silanes after hydrolysis.
[0026] Figure 6 This is a graph showing the change in solid content of the composition in Table 2 as the composition is cured by heating for a long time.
[0027] Figure 7 It is a graph showing the stability test results of Example 5 and Comparative Example 5. Figure 7 (a) represents TEOS and Et-OH, Figure 7 (b) represents MTES and Et-OH, Figure 7 (c) in FIG. 5 represents MTES and IPA. DETAILED DESCRIPTION
[0028] Hereinafter, the present invention will be described in detail.
[0029] The present invention relates to a composition for forming a back electrode, which comprises a water-based conductive polymer solution, a binder and a solvent.
[0030] In one aspect, the adhesive is a mixture of MTES (methyl triethoxy silane) and DMDES. Preferably, the adhesive is mixed with 5 to 15 parts by weight of DMDES solids based on 100 parts by weight of MTES solids.
[0031] Preferably, the adhesive is a silane compound, and in particular, the adhesive may be one or more compounds selected from the group consisting of alkoxysilanes, vinylsilanes, epoxysilanes, methacryloxysilanes, isocyanate silanes and fluorosilanes.
[0032] Preferably, the binders are of the type silazanes, silanes and siloxanes. Examples of the compound include methyltrichlorosilane (MTS), tetraethoxysilane (TEOS), tetramethylorthosilscate (TMOS), hexamethyldisiloxane (HMDSO), methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), vinyltrimethoxysilane (VTMS), vinyltriethoxysilane (VTES), diethylvinylsilane (DEVS), ethylmethoxysilane (EMS), tetramethylsilane (TMS), ethyltrimethoxysilane (ETMS), tetraethoxysilane (TES), triethylsilane (TES), any one of dimethyldiethoxysilane (DMDES), cyclohexylmethyldimethoxysilane (CMDMS), dicyclophentyldiphenyldimethoxysilane (DCDMS), phenyltriethoxysilane (PES), diphenyldimethoxysilane (DPDMS), tetramethyldisiloxane (TMDSO), hexamethyltrisiloxane (HMTSO), tetramethylcyclotetrasiloxane (TMCTS), hexamethyldisilazane (HMDSN), or a mixture of two or more thereof,The most preferred is a mixture of MTES (methyl triethoxy silane) and DMDES (dimethyldiethoxy silane). Preferably, the adhesive is mixed with 5 to 15 parts by weight of DMDES solids based on 100 parts by weight of MTES solids.
[0033] In one aspect, the solvent is isopropyl alcohol (IPA).
[0034] The solvent can be one or more selected from the group consisting of methanol, ethanol, isopropanol, ethylene glycol, butanediol, neopentyl glycol, 1,3-pentanediol, 1,4-cyclohexanedimethanol, diethylene glycol, polyethylene glycol, polybutylene glycol, dimethylolpropane, trimethylolpropane, propylene glycol monomethyl ether, n-methylpyrrolidone, dimethyl sulfoxide and water, preferably, it can be isopropyl alcohol (IPA).
[0035] On the one hand, the conductive polymer is Pedot-PSSA. The conductive polymer can be one or more compounds selected from the group consisting of polyaniline polymers, polypyrrole polymers and polythiophene polymers, preferably poly (3,4-ethylenedioxythiophene) (Pedot) as a polythiophene polymer. The dopant can be selected from one or more compounds in the group consisting of dodecylbenzenesulfonic acid, toluenesulfonic acid, camphorsulfonic acid, benzenesulfonic acid, hydrochloric acid, styrenesulfonic acid, 2-acrylamide-2-methylpropanesulfonic acid, 2-sulfosuccinate salt, isophthalic acid-5-sodium sulfonate, dimethyl isophthalate-5-sodium sulfonate and 5-sodium sulfonate-di-(β-hydroxyethyl isophthalate), preferably poly (sodium 4-styrene sulfonate) or PSS. Preferably, the dopant is mixed with the polymer for use, and most preferably PEDOT-PSS is obtained by adding PSS as an anion dopant to PEDOT.
[0036] When MTES (trifunctional) is used instead of TEOS (tetrafunctional), MTES is a substance with a lower polarity than TEOS and therefore has a lower compatibility with water than TEOS.
[0037] In the present invention, in order to impart conductivity to the surface of the dried coating film, a conductive polymer (Pedot-PSSA aqueous dispersion) may be used in an amount of at least 20 to 30% by weight (in parts by weight, 20 to 30 g relative to 100 g of the composition) in 100% by weight of the entire composition. Preferably, 25% by weight of the conductive polymer may be used.
[0038] In one aspect, the composition comprises: 20 to 30 wt % of the water-based conductive polymer solution; 2 to 5 wt % of the binder; and 65 to 75 wt % of the solvent. Preferably, the composition comprises: 20 to 25 wt % of the water-based conductive polymer solution; 2 to 5 wt % of the binder; and 70 to 73 wt % of the solvent. In one aspect, the solid content of the conductive polymer is 14 to 21 parts by weight based on 100 parts by weight of the binder solid content.
[0039] In addition, preferably, the solid content of the binder should be in the range of 2% to 2.5% in 100 g of the entire composition.
[0040] Containing 25 g of a conductive polymer (1.4% solids, 98.6% water content) in 100 g of the composition is equivalent to containing about 25 g of water in 100 g of the composition.
[0041] In addition, the present invention relates to a method for manufacturing a composition for forming a back electrode, which includes: a) a step of mixing a binder and a solvent to prepare a mixed solution; b) a step of adding a conductive polymer solution to the mixed solution; and c) a step of hydrolyzing the conductive polymer and the binder in the solution manufactured in step b).
[0042] In one aspect, the step c) is reacted for more than 24 hours.
[0043] If the time is shorter than 24 hours, there is a possibility that sufficient hydrolysis may not occur, so it is preferable to ensure a sufficient time.
[0044] In addition, the present invention relates to a method for manufacturing a back electrode, which includes: a) a step of coating a composition for forming a back electrode on a substrate; b) a step of heating and curing the coated substrate; and c) a step of reacting the composition in such a way that it has a three-dimensional network structure through a condensation reaction.
[0045] On the one hand, preferably, the step b) is cured by heating at 110 to 130° C. for 2 to 4 hours, or by heating at 140 to 160° C. for 1 to 3 hours. The temperature and time ranges are the best ranges after experiments on the physical properties of pencil hardness and surface resistance, taking into account high hardness and low surface resistance values.
[0046] On the one hand, the pencil hardness of the back electrode is greater than 7H and the surface resistance is less than 10_7.
[0047] The coating method on the substrate can be any conventional coating method in the art without limitation, and preferably, it can be spray coating, roller coating, dip coating, etc.
[0048] <Selection of adhesive>
[0049] Among the inorganic substances used as existing adhesives, tetraethoxysilane (TEOS, Tetra-EthylOrtho-Silicate) is a representative substance as a silane coupling agent, which has four alkoxy groups (TEOS is an ethoxy group). Water is added (added) while adding an acid catalyst, so that the four alkoxy groups (ethoxy groups) can be decomposed into four alcohols (ethanol), and this reaction is collectively referred to as the hydrolysis reaction of TEOS. The hydrolyzed TEOS generates -OH at the position of the alkoxy group, and finally forms four hydroxyl groups (-OH). TEOS before hydrolysis is a water-insoluble substance and does not mix directly with water. However, the alkoxy group at the molecular end of the hydrolyzed TEOS is replaced by a hydroxyl group (-OH), thereby increasing the polarity and the hydrophilicity, thereby becoming a substance that can be stably mixed with water. In other words, the hydrophilicity of the hydrolyzed TEOS also increases, thereby becoming a substance that can be stably mixed with water.
[0050] Figure 1 The graph shows the change in the molecular structure of TEOS before and after hydrolysis. At this time, the molecular weight of the TEOS molecule changes (decreases) from 208.33 g / mol (before hydrolysis) to 96.114 g / mol (after hydrolysis) due to the hydrolysis reaction.
[0051] Although the substance (Si-(OH)4) produced after hydrolysis has a chemical structure that is significantly different from that of TEOS (Si-(OCH2CH3)4) before hydrolysis, it is referred to as "TEOS (Si-(OH)4) after hydrolysis". Under high-temperature heating and drying conditions, the hydrolyzed TEOS (Si-(OH)4) undergoes a dehydration condensation reaction as water and solvents evaporate, thereby undergoing a cross-linking reaction and ultimately forming a high-hardness cured coating film. Figure 2 As shown in the example of the dehydration condensation reaction of TEOS (Si-(OH)4) after hydrolysis, as one dehydration condensation reaction proceeds, TEOS (Si-(OH)4) releases one molecule of H2O and shares one O (oxygen). Therefore, when calculating based on two molecules of TEOS (Si-(OH)4) after hydrolysis, one dehydration condensation reaction will produce a decrease in mass, and the reduced mass is equivalent to the molecular weight of one molecule of water (H2O) after dehydration.
[0052] The decrease in molecular weight by dehydration condensation can be defined as n×(1 / 2)×(molecular weight of H2O), where n is the number of dehydration condensations.
[0053] When all four -OH groups in TEOS are dehydrated and condensed, four water molecules are produced. When calculated based on one Si group, this is equivalent to reducing the molecular weight of the hydrolyzed TEOS (Si-(OH)4) (MW: 96.114 g / mol) by 1 / 2 of the dehydrated water molecules.
[0054] At this time, the reduced weight can be defined as the number of reactive groups × 0.5 × the molecular weight of water. Since four reactive groups undergo dehydration reaction, it can be calculated by 4 × 0.5 × 18.015 g / mol = 36.03 g / mol.
[0055] The situation where all reactive groups (-OH) of the hydrolyzed TEOS (Si-(OH)4) are completely dehydrated and condensed can be defined as the dry coating being "completely cured". At this time, the measured net weight is the molecular weight of the dehydrated and condensed TEOS (Si-O2).
[0056] Figure 3 Schematic diagram showing a dried (cured) TEOS coating film after a dehydration condensation reaction. At this time, the molecular weight of each molecule of completely cured TEOS (dehydration condensed TEOS (Si—O 2 )) can be 60.084 g / mol.
[0057] The molecular weight of TEOS (Si-(OCH2CH3)4) before hydrolysis is 208.33 g / mol, and the molecular weight of TEOS (Si-(OH)4) after hydrolysis is 96.114 g / mol, which is 54% less than that of TEOS before hydrolysis. After complete curing, the molecular weight of TEOS (Si-O2) is 60.084 g / mol (=96.114 g / mol-36.03 g / mol), which is about 72% less than that of TEOS before hydrolysis.
[0058] Under ideal conditions, when TEOS is completely solidified through hydrolysis and dehydration condensation reactions, the solid content of the completely solidified TEOS (Si-O2) after hydrolysis can be calculated to be approximately 28.84% compared to the TEOS (Si-(OCH2CH3)4) before hydrolysis (solid content = molecular weight after dehydration condensation / molecular weight before hydrolysis × 100 = 60.084 g / 208.33 g × 100).
[0059] This means that if 100 g of TEOS (Si-(OCH2CH3)4) before hydrolysis, which acts as a binder in the water-soluble coating liquid composition, is added, 28 g of solid matter can be obtained in the dried coating film.
[0060] Based on the above-described common knowledge, in the dehydration condensation reaction of TEOS, the change in the reduction of the solid content according to the progress stage of the dehydration condensation reaction can be sorted out in more detail.
[0061] Tetrafunctional TEOS can undergo four dehydration condensation reactions, and these reactions were divided into stages to calculate the change in average molecular weight. The results are shown in the table below.
[0062] Table 1
[0063]
[0064] Table 1 above shows calculated values of changes in molecular weight (g / mol) and solid content (%) according to hydrolysis and dehydration condensation of TEOS. Figure 4 It is a graph showing the change of solid percentage (%) with the number of dehydration condensation reactions. The solid content (%) value of TEOS dehydration condensation in the second stage is 37.49%, and the solid content (%) value in the third stage is 33.16%. Calculating and predicting the change of solid content based on each reaction stage can be an important basis for confirming the two indicators of the coating solution.
[0065] First, the solidification state of the dried coating film. After the coating liquid is prepared, the solid content is measured, which is the basis for understanding the progress of the dehydration condensation of the dried coating film.
[0066] Secondly, the curing conditions for achieving the theoretical final solid content can be mastered, that is, the optimal heating temperature and heating curing time required to achieve complete curing of the coating film can be mastered.
[0067] Optimization of curing conditions
[0068] In order to optimize the curing conditions and confirm the relationship between the drying temperature and time and the degree of crosslinking, an experiment was conducted using the composition shown in Table 2 below by measuring the change in solid content over time at various drying temperatures using TEOS as a reference.
[0069] Table 2
[0070] % Remark Ethanol 81.313 TEOS (NV=28.84%) 13.870 (NV=28.84%) Deionized water 4.797 35% HCL aqueous solution 0.020 total 100.00 NV(%)Theoretical value 4
[0071] The solid content values at various temperatures of the dehydration condensation heating curing were measured using the composition in Table 2. The results are as follows: Figure 6 As shown. According to the above results, the theoretical solid content value of 28.84% that can be achieved when TEOS is 100% dehydrated and condensed is not reached in all temperature ranges. However, the dry coating film (300nm) of the TEOS composition can also meet the hardness of 9H under the conditions of 120°C and curing for 1 hour. However, it can be confirmed that under this condition, a large amount of undehydrated (uncured) TEOS may remain.
[0072] Based on this, it can be judged that only TEOS with four reactive functional groups can achieve high hardness. Generally, when a composition is prepared using silanes with three or fewer functional groups and then heated and cured for drying, the pencil hardness of the dried coating is about 3H. Since the functional groups that can induce dehydration condensation reactions of almost all silanes and silane derivatives except TEOS are three or fewer functional groups, it is judged that these are not actually tested. The drying characteristics of the composition using TEOS as an adhesive obtained through the preliminary experiment of the present invention are as follows:
[0073] 1) When the heating curing temperature of the composition is 200°C, the crosslinking degree of the dried coating film can reach the third stage within 2 hours of drying time.
[0074] 2) When the heat curing temperature of the composition is 200° C. or lower (eg, 120° C., 150° C.), the degree of crosslinking in the dried coating film of the composition reaches between the second stage and the third stage.
[0075] 3) When the heating temperature is low and the heating time is short so that the crosslinking degree of the composition is close to the second stage, the dried coating film will not have cracks.
[0076] 4) When the heating time is prolonged or the heating temperature is increased, the crosslinking degree of the dried coating film moves toward the third stage.
[0077] 5) When the crosslinking degree of the dried coating film is very close to the third stage or exceeds the third stage, cracks appear.
[0078] 6) When the degree of crosslinking exceeds the second stage and reaches an unspecified point in the third stage, the hardness of the dried coating film is 9H. In other words, the hardness of the dried coating film does not become 9H only when the degree of crosslinking reaches the fourth stage.
[0079] From a general point of view, for general organic polymers (polymer compounds) that solidify by forming a three-dimensional network structure, the distance between the functional groups that undergo cross-linking reactions is very far. In addition, the farther the distance between the cross-linking reaction groups, the more the flexibility of the dry coating increases and the lower the hardness. This is why the hardness of the dry coating formed by the cross-linking reaction of organic substances usually reaches about 3H, and it is classified as a high-hardness dry coating.
[0080] In the previous experiments, it was confirmed that the reason why the hardness of the dried coating film of the inorganic composition using TEOS is high is that the TEOS composition as a tetrafunctional group presents the fourth stage of crosslinking degree in the dried coating film and reaches a hardness of 9H. This is a prejudice. TEOS does not present high hardness because of the large number of reactive groups crosslinked by dehydration condensation, but because the distance between the functional groups of dehydration condensation is very close, which makes the distance between the "crosslinking points" crosslinked by dehydration condensation in the dried coating film very close and dense, resulting in high hardness. In fact, the crosslinking degree is sufficient to reach a hardness of 9H when it is in the range of the second stage to the third stage, and it is not necessarily the fourth stage that can reach a hardness of 9H.
[0081] This confirms that due to the characteristics of the dried TEOS coating with high hardness and severe shrinkage, when the degree of crosslinking exceeds the third stage, the hardness of the dried coating may continue to increase, but cracks will appear. Therefore, from the perspective of maintaining stable coating performance, this is undoubtedly a very unfavorable condition.
[0082] For a dried coating film of tetrafunctional TEOS, heat curing conditions can be set to achieve a crack-free hardness of 9H. However, it is difficult to artificially prevent changes in the degree of crosslinking that occur during storage or distribution of the dried coating film after heat curing.
[0083] As a solution capable of solving these problems occurring in the dried coating film, the present invention attempts to solve this problem by using trifunctional silane instead of tetrafunctional TEOS.
[0084] For this purpose, methyltriethoxysilane (Methyl Tri-Ethoxy Silane, Tri EthoxyMmethylSilane, hereinafter referred to as "MTES"), which has a similar molecular weight among trifunctional silanes, was selected.
[0085] As the difunctional silane for adjusting the degree of crosslinking, dimethyl diethoxy silane (DMDES) having a similar molecular weight was selected.
[0086] Table 3 below shows the structural formulas and molecular weights of trifunctional silanes and difunctional silanes.
[0087] Table 3
[0088]
[0089] Table 4 below is a calculation table showing the change in molecular weight (solid content (%)) due to dehydration condensation of silanes after hydrolysis.
[0090] Table 4
[0091]
[0092] When hydrolysis is performed by mixing trifunctional silane and difunctional silane, in order to calculate the theoretical final crosslinking degree of the mixed composition, the crosslinking degree was calculated by the following method.
[0093] The dehydration condensation crosslinking degree was calculated by assuming that the dehydration condensation crosslinking degree of the difunctional group is at most the second stage and the dehydration condensation crosslinking degree of the trifunctional group is at most the third stage.
[0094] Regarding the calculation method, when calculating the degree of crosslinking, substances used for other purposes such as conductive polymers are excluded from the total solid content of the composition. Based on the theoretical solid content of the pure inorganic adhesive being 100 parts by weight, the final degree of crosslinking of the adhesive mixture is calculated by the method of solid content of MTES (%) × 3 + solid content of DMDES (%) × 2 in the estimated total solid content of the adhesive.
[0095] [Mathematical formula 1]
[0096] Method for calculating the degree of crosslinking of a composition
[0097]
[0098] The cross-linking value of the experimental example was calculated using the above-mentioned calculation method.
[0099] <Improvement of storage stability>
[0100] In addition to improving the change of the dried coating film over time, the conductive polymer composition based on hydrolyzed TEOS has a very short shelf life in the liquid state while maintaining stable physical properties. Compared with the general composition of a water-based polymer and a conductive polymer having an average storage stability of more than 6 months, it cannot be determined that the short shelf life of the inorganic binder and conductive polymer composition is caused by the instability of the conductive polymer.
[0101] The reason why the inorganic binder and the conductive polymer composition have a very short shelf life is more reasonably considered to be due to the dehydration condensation of the hydrolyzed inorganic binder in the liquid at room temperature.
[0102] In this study, when the hydrolyzed TEOS and conductive polymer compositions were stored at room temperature (25°C), refrigerated (4°C), and warm (60°C), the storage stability of the liquids showed a very large difference. This is believed to be caused by the following reasons: when the temperature rises, the speed of dehydration condensation in the liquid composition increases, and when the temperature drops, the dehydration condensation reaction speed slows down due to the decrease in reactivity.
[0103] It has been confirmed in previous studies that in order to improve the storage stability of the composition produced in this study, the content of the catalyst needs to be reduced to the greatest extent, and this has become a factor in improving the storage stability of the composition. It can be fully predicted that on this basis, by using a refrigerated storage method to reduce the storage temperature of the composition during the circulation process of the composition, the shelf life of the composition can be extended.
[0104] The four silanes have similar structures after hydrolysis. Figure 5 is a simple schematic diagram of the structure.
[0105] Reference Figure 5 , that is, the spatial occupancy form of the hydroxyl group (-OH) may vary depending on the size of the alkyl group, which affects the "reaction rate" in the dehydration condensation reaction.
[0106] Regarding the hydrolysis product of triethylsilane (TES) having a very small hydrogen atom (H) at the position of the R group, the three hydroxyl groups (-OH) in its molecular structure are likely to be widely distributed in a roughly planar position. In addition, it is expected that the dehydration condensation reaction between different molecules proceeds faster than that of other trifunctional silanes compared in this study.
[0107] On the contrary, when the size of the R group is very large, that is, the three hydroxyl groups (-OH) in the molecular structure of the hydrolyzate of 3-glycidyloxypropyltriethoxysilane (3-GPTES) will be reduced to a very small space and distributed. In addition, it can be predicted that the dehydration condensation reaction between the hydrolyzate molecules will be very slow.
[0108] Finally, as the size of the R group increases, the phenomenon that the rate of the dehydration condensation reaction slows down has a greater impact on the second stage of the dehydration condensation reaction than on the first stage, and an even greater impact on the third stage of the dehydration condensation reaction.
[0109] This means that when a hydrolysis product having a large R group size is heat-cured, drying of the coating becomes very slow or a heating temperature higher than the average temperature may be required, but conversely, the dehydration condensation reaction occurring in the liquid at room temperature is very slow, and therefore, this may become a more effective method for improving the room temperature storage stability of the liquid.
[0110] This may be the reason that fully explains the phenomenon that the hydrolyzed composition of trifunctional or difunctional silanes has excellent storage stability at room temperature compared with the hydrolyzed product of tetrafunctional TEOS.
[0111] <Solvent Selection>
[0112] TEOS before hydrolysis is incompatible with water, but the four hydroxyl groups (-OH) of TEOS after hydrolysis are replaced and hydrophilicity is increased, so it has good compatibility with water. Different from this, after hydrolysis of MTES, which is a trifunctional group, three hydroxyl groups (-OH) are replaced, and a methyl group (-CH3) remains. Therefore, the compatibility with water after hydrolysis is not as good as TEOS. In order to solve this problem, a method of reducing the content of water and increasing the content of solvent can be considered, but since the content of water provided to the present composition refers to the content of water contained in the conductive polymer, it is difficult to artificially adjust the content of water.
[0113] In order to improve the stability of the hydrolyzed MTES aqueous solution, in the composition prepared in the present invention, the relative stability is improved by using IPA having a higher solubility than ethanol.
[0114] <Selection of Conductive Polymer>
[0115] Conventional Pedot-PSSA aqueous dispersions commercially available as polythiophene polymer dispersions have the following characteristics:
[0116] ○Solid content (NV%): about 1.5%
[0117] ○Average particle size (size, nm): 100nm or less
[0118] ○ pH (25°C): Acidic solution below 2.
[0119] ○Solvent: water content is more than 98%.
[0120] The dopant of the Pedot-PSSA aqueous dispersion is unneutralized polystyrene sulfonic acid (PSSA) or polystyrene sulfonic acid (PSS) neutralized with an alkaline substance such as Na.
[0121] In the present invention, it is intended to use a conductive polymer aqueous dispersion prepared by using polystyrene sulfonic acid (PSSA) in an acidic state which is not neutralized in various commercially available Pedot-PSSA-based conductive polymer aqueous dispersions as a dopant.
[0122] Such an aqueous conductive polymer dispersion is generally a strongly acidic substance having a pH of 2 or less, and thus can smoothly function as an acidic catalyst required in a hydrolysis process that requires a catalyst when producing the composition.
[0123] In order to manufacture the composition, the existing prior art generally uses a catalyst, which plays a role in promoting the hydrolysis reaction of the binder substance. All kinds of acidic substances can be used as catalysts. As a standard acid catalyst, an aqueous solution of hydrochloric acid is generally used. However, in recent years, in order to avoid environmental regulations on halogen compounds, inorganic acids such as sulfuric acid and phosphoric acid are used, or organic acids such as formic acid and acetic acid are used. However, due to the use of catalysts, various problems arise, as a result of which: 1) As the catalyst content increases, the storage stability of the liquid state deteriorates rapidly; 2) As the catalyst content increases, seeding and precipitation occur faster; 3) As the catalyst content increases, the surface resistance deteriorates rapidly.
[0124] On the contrary, the best storage stability was shown even though the acidic substance of the present invention, i.e., the Pedot-PSSA aqueous dispersion, was used as a catalyst and no other catalyst was used. This is because when the acidic substance, i.e., the Pedot-PSSA aqueous dispersion, was used as a catalyst to produce the composition, the heat generated during the hydrolysis reaction of the composition was low and the reactivity was low, so there was a problem of a longer production process, but based on this, it was confirmed that in order to achieve storage stability of the composition, it is not necessary to use a catalyst.
[0125] [Example 1 and Comparative Example 1]
[0126] In order to confirm the storage stability of the type of adhesive according to the present invention, the compositions of the embodiments and comparative examples were manufactured with the composition shown in Table 5 below. Regarding the TEOS input, the estimated solid content (%) was calculated at 33.16% based on the third stage of crosslinking degree. The higher the inorganic adhesive content of the composition, the faster the storage property deteriorates. In order to compare the storage property of the composition and the tendency of cracks to occur in the dried coating film, the composition was manufactured with a solid content (%) of 5%. In order to accurately observe the stability of the liquid state, water was used in the amount of conductive polymer expected to be used, thereby replacing the colored conductive polymer. The water content required for hydrolysis is marked as Di-water (deionized water) (1), and water is additionally added to adjust the deviation of the water content between the comparative test groups to the same content, and it is marked as Di-water (2). 0.02% of a 35% hydrochloric acid aqueous solution was used as a catalyst. The hydrolysis was carried out at room temperature for 25 hours.
[0127] Table 5
[0128]
[0129] [Experimental Example 1]
[0130] <1-1> Comparison of liquid storage stability of compositions based on silane functional groups (based on 5% solid content)
[0131] In order to observe the liquid storage properties of Example 1 and Comparative Example 1, the compositions in Table 5 were stored at room temperature. The results are shown in Table 6 below.
[0132] Table 6
[0133]
[0134] As shown in Table 6, the triethoxy silane (TES) hydrolyzate of Comparative Example 1-1 produced gel at a much faster rate than the tetraethoxy silane (TEOS) hydrolyzate of Comparative Example 1-2.
[0135] Compared with the hydrolyzate of tetraethoxysilane (TEOS), the hydrolyzate of methyltriethoxysilane (MTES) of Example 1 exhibits significantly improved storage stability at room temperature.
[0136] Compared with methyltriethoxysilane (MTES) and tetraethoxysilane (TEOS), 3-glycidyloxypropyltriethoxysilane (3GPTES) of Comparative Examples 1-3 exhibits very excellent solution storage stability, and can maintain stability even when the storage period exceeds 6 months.
[0137] <1-2> Dry coating thickness and crack test method of Example 1 and Comparative Example 1
[0138] The composition was applied to a tempered glass with a thickness of 5 mm and a size of 150 mm × 150 mm using a Baker Applicator YBA-3 with a wet film thickness of 12.5 μm. No preheating process was performed, and heat curing was performed immediately after coating according to various drying temperatures. Regarding the heat curing conditions, curing was performed at room temperature (25°C), and then the temperature was increased by 20°C from 60°C to 200°C for 1 hour. The theoretical final dry coating thickness when the specific gravity value of the liquid is not corrected is defined as the wet film thickness × solid content (%). In this experiment, it is assumed that the thickness of the dry coating is 12.5 μm × (5 / 100 (%)) = 0.625 μm = about 625 nm. When no cracks appeared after drying, the drying state was predicted by measuring the pencil hardness. When cracks appeared, the pencil hardness was not measured.
[0139] These are the pencil hardness and crack test results of Example 1 and Comparative Example 1 at various temperatures. The dry coating film thickness is about 600-650 nm.
[0140] Table 7
[0141]
[0142] Note: × = cannot be measured
[0143] <1-3> Pencil hardness and crack test
[0144] This is the pencil hardness and crack test result of Example 1 and Comparative Example 1 when heat cured at 120°C. The dry coating film thickness is about 600-650 nm.
[0145] Table 8
[0146]
[0147] Note: × = cannot be measured
[0148] As shown in the results of Table 7 and Table 8, the triethoxysilane (TES) hydrolyzate was unstable because the liquid was turbid and had high viscosity after 24 hours of hydrolysis. In addition, when dried after coating, it showed a very fast drying speed, but the film-forming property was poor, so it was meaningless as a comparison group.
[0149] The hydrolyzate of tetraethoxysilane (TEOS) also showed a very fast drying speed under the drying condition of 60°C × 1 hour, and its drying degree was sufficient to measure the pencil hardness, but cracks appeared when the dried coating film was left at room temperature for a certain period of time.
[0150] The hydrolyzed product of tetraethoxysilane (TEOS) showed no cracks at a dry film thickness of about 300 nm under drying conditions of 120°C for 1 hour, but as shown in this experiment, cracks immediately appeared at a dry film thickness of about 600 nm under drying conditions of 120°C for 1 hour.
[0151] The hydrolyzate of methyltriethoxysilane (MTES) showed no cracks when the dry film thickness was about 600 nm and the temperature was heated to 150° C. for 1 hour. However, considering the low hardness of the dry film, it can be confirmed that the dehydration condensation reaction is significantly slower than that of the hydrolyzate of tetraethoxysilane (TEOS).
[0152] 3-Glycidyloxypropyltriethoxysilane (3GPTES) did not dry under the conditions of heat curing for 1 hour at a temperature below 120°C. The pencil hardness of 7H was measured under the heat curing conditions of 150°C × 2 hours or 180°C × 1 hour, and the pencil hardness of 8H was measured under the heating conditions of 120°C × 24 hours.
[0153] Therefore, it can be confirmed from the above results that, preferably, as a binder, trifunctional MTES is mainly used instead of tetrafunctional TEOS, and in order to adjust the crosslinking degree of the dried coating film, a small amount of difunctional DMDES is mixed to reduce the crosslinking degree of the entire dried coating film, thereby achieving a high hardness dried coating film and preventing cracks to the greatest extent.
[0154] [Example 2 and Comparative Example 2]
[0155] In order to conduct a stability comparison experiment of an aqueous solution of a TES hydrolyzate according to the solvent type of the composition, the Et-OH and IPA compositions shown in the following Table 9 were respectively prepared. In order to confirm transparency, water and a hydrochloric acid catalyst were used to replace 25% of the Pedot-PSSA aqueous dispersion to prepare a hydrolyzate.
[0156] Table 9
[0157]
[0158] [Experimental Example 2]
[0159] The stability comparison results are as follows Figure 7 As shown in Figure 2, they represent (a) TEOS and Et-OH, (b) MTES and Et-OH, and (c) MTES and IPA.
[0160] Regarding the compatibility and stability of MTES hydrolyzate containing about 25% water, it is more stable when mixed with isopropyl alcohol (IPA) than when mixed with ethanol (Et-OH). In addition, there are no other side effects that may be caused by high-boiling point solvents, and there is no side effect on increasing the drying speed of inorganic adhesives.
[0161] [Example 3 and Comparative Example 3]
[0162] In order to evaluate the effect of the catalyst on the manufactured composition, surface resistance and storage experiments were conducted with the composition in Table 10 below, and the results are shown in Table 10.
[0163] Table 10
[0164] serial number distinguish Comparative Example 3-1 Comparative Example 3-2 Example 3 1 Ethanol 656.16 656.46 656.66 2 TEOS (NV=28.84%) 69.35 69.35 69.35 3 Deionized water 23.99 23.99 23.99 4 35% HCL aqueous solution 0.500 0.20 0.00 5 Huclawn N3 250.00 250.00 250.00 total 1000.00 1000.00 1000.00 TEOS NV (%) theoretical value 2.00 2.00 2.00 Conductive polymer NV (%) 0.35 0.35 0.35 NV(%)Total 2.35 2.35 2.35
[0165] [Experimental Example 3]
[0166] <3-1>Surface resistance and liquid stability test
[0167] These are the surface resistance and liquid stability test results of Example 3 and Comparative Example 3.
[0168] Table 11
[0169]
[0170] As described above, in the coating test conducted every other week since the storage of the composition, the surface resistance of the dried coating film of the comparative example rapidly deteriorated as the catalyst content increased.
[0171] On the contrary, Example 3 used the acidic substance of the present invention, namely the Pedot-PSSA aqueous dispersion, as a catalyst, and did not use a separate catalyst, but showed the most excellent storage stability. Based on this, it was concluded that when the acidic substance, namely the Pedot-PSSA aqueous dispersion, was used as a catalyst to manufacture the composition, the heat generated during the hydrolysis reaction of the composition was low, and there was a problem of a longer manufacturing process due to low reactivity, but in order to achieve storage stability of the composition, it is preferred not to use a catalyst.
[0172] [Example 4 and Comparative Example 4]
[0173] In order to observe the hardness and surface resistance according to the content of the conductive polymer, a composition was manufactured using the composition of Example 4 shown in Table 12 below.
[0174] Table 12
[0175]
[0176] [Experimental Example 4]
[0177] <4-1>Measurement of pencil hardness
[0178] This is the result of measuring the pencil hardness under the heating conditions of Example 4, and the thickness of the dried coating film is based on 250 to 300 nm.
[0179] Regarding the pencil hardness, evaluation was performed according to ISO 15184 by applying a load of about 750 g and scratching a pencil across the surface of the dried coating film, and the pencil hardness was confirmed by gradually increasing the load until obvious defects appeared on the coating film surface.
[0180] Table 13
[0181]
[0182] <4-2>Measurement of pencil hardness
[0183] This is the result of measuring the pencil hardness under the heating conditions of Example 4, and the thickness of the dried coating film is based on 250 to 300 nm.
[0184] Table 14
[0185]
[0186] <4-3> Surface resistance measurement
[0187] This is the result of measuring the surface resistance under the heating conditions of Example 4, and the thickness of the dried coating film is based on 250 to 300 nm.
[0188] The surface resistance was measured using SIMCO ST-4 (voltage: 100 V, Simco Co., Ltd., Japan).
[0189] The surface resistance is a logarithmic function, usually expressed in the form of a number * EX. In the present invention, it is expressed in the form of EX. The higher the measured value, the higher the surface resistance value, and the lower the measured value, the lower the surface resistance value.
[0190] Table 15
[0191]
[0192] <4-4> Surface resistance measurement
[0193] This is the result of measuring the surface resistance under the heating conditions of Example 4, and the thickness of the dried coating film is based on 250 to 300 nm.
[0194] Table 16
[0195]
[0196] By summarizing the above results, it can be confirmed that the physical properties of Examples 4-4 to 4-6 are best when the content is 20 to 30%, and the composition of Example 4-5 with a content of 25% exhibits the most excellent properties. The heating curing conditions are generally excellent under the conditions of curing at 110 to 130°C for 2 to 4 hours, or curing at 140 to 160°C for 1 to 3 hours, among which the most excellent properties are exhibited when curing at 150°C for 2 hours.
[0197] [Example 5 and Comparative Example 5]
[0198] In order to compare compositions according to the mixing ratio of MTES and DMDES, compositions shown in the following Table 17 were prepared by changing the DMDE solid content based on 100 g of MTES solid. The IPA content was adjusted so that the total amount would be 1000 g.
[0199] Adopted the method for direct hydrolysis of conductive polymer.As shown in the following table 17, in 2 liters of reaction vessels measuring weight, put into isopropyl alcohol (IPA) and MTES and DMDES before hydrolysis according to each composition ratio with specified amount, and stir with the linear velocity of 0.4m / s to prepare mixed solution (A).Prepare 250g conductive polymer aqueous solution, slowly join it in the isopropyl alcohol being stirred and TEOS mixed solution (A) before hydrolysis.The reaction vessel is sealed, and the linear velocity is adjusted to 0.8m / s, then stirred 24 hours at normal temperatures, to be hydrolyzed.After 24 hours, measure the gross weight of the reaction vessel that composition is housed, and by the weight of loss, isopropyl alcohol is supplemented in each composition respectively, then stir and mix.
[0200] Filter through a #300 mesh strainer and package in a plastic container.
[0201] Table 17
[0202]
[0203] In addition, for comparison with the composition of the mixed binder of the above MTES and the above DMDES, a composition of Comparative Example 5 as shown in the following Table 18 was prepared.
[0204] Table 18
[0205]
[0206] [Experimental Example 5]
[0207] Using Baker Applicator YBA-3, the compositions of Example 5 and Comparative Example 5 were coated on tempered glass with a thickness of 5 mm and a size of 150 mm×150 mm at a thickness of 12.5 μm. Preheat at 80°C for 15 minutes to evaporate the solvent. Heat at 120°C for 1 hour to induce curing. Measure the surface resistance and hardness, and repeat the step of heating and curing at 120°C for 1 hour three times. The theoretical final dry coating thickness when the liquid specific gravity value is not corrected is defined as the wet film thickness×solid content (%). In this experiment, the thickness of the dry coating is defined as 12.5 μm×(2.35 / 100(%))=0.294 μm=294 nm (about 300 nm).
[0208] <5-1> Crack comparison test
[0209] This is the result of a crack comparison experiment conducted under heating and curing conditions at 120°C.
[0210] Table 19
[0211]
[0212] (Note: × = cracks, △ = fine cracks.)
[0213] <5-2> Crack comparison test
[0214] This is the result of a crack comparison experiment under heating and curing conditions at 150°C.
[0215] Table 20
[0216]
[0217] (Note: × = cracks appear, △ = fine cracks)
[0218] <5-3>Measurement of pencil hardness
[0219] This is the result of measuring the pencil hardness under heat curing conditions at 120°C.
[0220] Table 21
[0221]
[0222] (Note: × = cannot be measured.)
[0223] <5-4>Measurement of pencil hardness
[0224] This is the measurement result of pencil hardness under heat curing conditions at 150°C.
[0225] Table 22
[0226]
[0227] (Note: × = cannot be measured.)
[0228] <5-5>Measurement of surface resistance (Ω / □)
[0229] This is the result of measuring the surface resistance (Ω / □) under the condition of heat curing at 120°C.
[0230] Table 23
[0231]
[0232] (Note: × = cannot be measured.)
[0233] <5-6> Measure surface resistance (Ω / □)
[0234] This is the result of measuring the surface resistance (Ω / □) under the condition of heat curing at 150°C.
[0235] Table 24
[0236]
[0237] (Note: × = cannot be measured.)
[0238] Regarding the following <5-7> and <5-8>, after the composition of the experimental example prepared for the storage test of Example 5 and Comparative Example 5 was prepared, it was re-coated every week and every 7 days for a total of four weeks, and then heat-cured at 120° C.×2 hr. The hardness and surface resistance were measured for each test piece to measure the changes in the physical properties of the composition.
[0239] <5-7> Storage Test
[0240] This is the storage test result of Example 5 and Comparative Example 5, which is the hardness measurement value (120°C x 2 hr).
[0241] Table 25
[0242]
[0243] (Note: × = cannot be measured.)
[0244] <5-8> Storage test results
[0245] This is the result of the storage test of Example 5 and Comparative Example 5, which is the surface resistance measurement value (120° C.×2 hr).
[0246] Table 26
[0247]
[0248] (Note: × = cannot be measured.)
[0249] The following <5-9> and <5-10> are experiments for testing the time-dependent changes of the dried coating films of Example 5 and Comparative Example 5. The compositions of the manufactured experimental examples were coated and heat-cured under the conditions of 120°C×2hr and 150°C×2hr. Each test piece was stored in an oven at a temperature of 80°C for 7 days (hours), and then the presence or absence of cracks was checked and the surface resistance was measured.
[0250] <5-9> Changes over time of the dried coating films of Example 5 and Comparative Example 5
[0251] This is the experimental result of the time-dependent change of the dried coating films of Example 5 and Comparative Example 5 under the heating and drying conditions of 120°C×2hr. The theoretical value of the dried coating film thickness is 294nm (about 300nm), which is the result measured after storage in an oven at 80°C×7 days (168hr).
[0252] Table 27
[0253]
[0254] (Note: × = cannot be measured, cracks appear, △ = fine cracks, ○ = no cracks (visual observation))
[0255] <5-10> Experiment on the change of dry coating film over time
[0256] This is the experimental result of the time-dependent change of the dried coating films of Example 5 and Comparative Example 5 under the heating and drying conditions of 150°C×2hr. The theoretical value of the dried coating film thickness is 294nm (about 300nm), which is the result measured after storage in an oven at 80°C×7 days (168hr).
[0257] Table 28
[0258]
[0259] (Note: × = cannot be measured, cracks appear, △ = fine cracks, ○ = no cracks (visual observation))
[0260] In the adhesive composition, the composition of Example 5 shows excellent effects in most physical properties and stability compared to Comparative Example 5, and in particular, the compositions of Examples 5-4 to 5-6 show the most excellent physical properties. Therefore, preferably, based on 100 g of MTES solids, the DMDES solids are 5 to 15 g.
[0261] The above experimental results confirm that when manufacturing a composition of a water-based conductive polymer dispersion (Pedot-PSSA aqueous dispersion) and a hydrolyzed inorganic binder, namely a silane compound, the composition manufactured by mixing a trifunctional silane inorganic substance with a mixed alkyl group substituted has low dehydration condensation reactivity and excellent room temperature storage performance compared to the composition manufactured by using a tetrafunctional TEOS.
[0262] Compared to the inorganic conductive polymer composition made using tetrafunctional TEOS, the inorganic conductive polymer composition made using the trifunctional silane inorganic compound with a mixed alkyl group being substituted has low reactivity, and therefore the heat curing time required for the heat curing temperature for dehydration condensation is longer than that of the tetrafunctional composition. If the heat curing time cannot be extended, the curing temperature needs to be increased.
[0263] When the dried coating film coated with the inorganic composition having excellent room temperature stability is cured by heating under sufficient conditions, the generation of cracks can be suppressed, and the change of the dried coating film over time is also small. The dried coating film of the composition of mixed MTES and DMDES is more stable than the dried coating film of the composition using MTES alone. At this time, based on the degree of crosslinking, the range of the stable mixing ratio can be more than 2.8 and less than 3.0. More preferably, it is stable in the range of 2.9.
[0264] The above experimental results confirm that, based on 150 degrees and curing for 2 hours, the present composition exhibits the following characteristics: surface resistance is less than 10_6, hardness is more than 7H, and the surface resistance of the dry coating changes over time after storage at 80°C for 168 hours is less than 10_7. Therefore, compared with the existing TEOS, the present composition exhibits excellent physical properties.
Claims
1. A composition for forming a back electrode, wherein: The composition for forming a back electrode comprises: Water-based conductive polymer solution; Adhesives; and Solvents, The adhesive is a mixture of MTES (methyl triethoxy silane) and DMDES. The adhesive contains 5 to 15 parts by weight of DMDES solids based on 100 parts by weight of MTES solids. The solvent is isopropyl alcohol (IPA), The water-based conductive polymer is Pedot-PSSA, The composition for forming a back electrode comprises: 20 to 30 wt % of the water-based conductive polymer solution; 2 to 5 wt % of said binder; and 65 to 75% by weight of said solvent, The composition for forming a back electrode does not contain any catalyst other than the water-based conductive polymer.
2. The composition for forming a back electrode according to claim 1, wherein Based on 100 parts by weight of the solid content of the binder, the solid content of the water-based conductive polymer is 14 to 21 parts by weight.
3. A method for producing a composition for forming a back electrode, which is the method for producing a composition for forming a back electrode according to claim 1, wherein: The method for manufacturing the composition for forming a back electrode comprises: a) a step of mixing a binder and a solvent to prepare a mixed solution; b) adding a conductive polymer solution to the solution; and c) a step of hydrolyzing the conductive polymer and the binder, The step c) is reacted for more than 24 hours.
4. A method for manufacturing a back electrode, wherein: The manufacturing method of the back electrode comprises: a) applying the composition for forming a back electrode according to claim 1 to a substrate; b) heating and curing the coated substrate; and c) a step of reacting the composition in such a manner that the composition has a three-dimensional network structure through a condensation reaction.
5. The method for manufacturing a back electrode according to claim 4, wherein: The step b) is performed by heating and curing at 110 to 130° C. for 2 to 4 hours, or heating and curing at 140 to 160° C. for 1 to 3 hours.
6. The method for manufacturing a back electrode according to claim 4, wherein: The pencil hardness of the back electrode is above 7H, and the surface resistance is 10 7 Ω / □ or less.
Citation Information
Patent Citations
Electroconductive coating composition, manufacturing method of the composition and electroconductive coatings
CN104293009A
Transparent conductive film, coating composition for forming same, and method for manufacturing transparent conductive film
CN109575760A